1989
DOI: 10.1172/jci113866
|View full text |Cite
|
Sign up to set email alerts
|

Role of endotoxemia in cardiovascular dysfunction and mortality. Escherichia coli and Staphylococcus aureus challenges in a canine model of human septic shock.

Abstract: Using different types of bacteria and a canine model simulating human septic shock, we investigated the role of endotoxin in cardiovascular dysfunction and mortality. Either Escherichia coli (a microorganism with endotoxin) or Staphylococcus aureus (a microorganism without endotoxin) were placed in an intraperitoneal clot in doses of viable or formalin-killed bacteria. Cardiovascular function of conscious animals was studied using simultaneous radionuclide heart scans and thermodilution cardiac outputs. Serial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(78 citation statements)
references
References 25 publications
(37 reference statements)
5
72
0
1
Order By: Relevance
“…However, one of the most striking findings in the study was that depression of the left ventricular ejection fraction, as well as the observed acute left ventricular dilatation, were reversible and returned to normal levels after 7 to 10 days in surviving patients (13). This was later confirmed in further patient studies and experimental settings (14)(15)(16)(17). In more recent studies, predominantly using echocardiography, cardiac dysfunction during sepsis and septic shock has been confirmed (18)(19)(20)(21).…”
Section: Introductionsupporting
confidence: 52%
“…However, one of the most striking findings in the study was that depression of the left ventricular ejection fraction, as well as the observed acute left ventricular dilatation, were reversible and returned to normal levels after 7 to 10 days in surviving patients (13). This was later confirmed in further patient studies and experimental settings (14)(15)(16)(17). In more recent studies, predominantly using echocardiography, cardiac dysfunction during sepsis and septic shock has been confirmed (18)(19)(20)(21).…”
Section: Introductionsupporting
confidence: 52%
“…[3][4][5] Several previous studies have shown that sepsisassociated cardiac dysfunction is primarily related to circulating myocardial depressant factors, including tumor necrosis factor (TNF)-. 15 However, because TNF-is a sentinel, rapid-response cytokine and is removed from the circulation several days before the resolution of myocardial dysfunction, it is clear that there are other mediators involved.…”
Section: Discussionmentioning
confidence: 99%
“…1 Experimental studies indicate that the pattern of cardiac dysfunction observed in Gram-negative sepsis is also encountered in Grampositive sepsis. 2 Supporting these finding are clinical data showing that ejection fraction recorded in humans with Gram-positive or Gram-negative sepsis does not differ significantly. 3,4 Although these studies suggest that Grampositive and Gram-negative bacteria activate analogous signaling pathways in the heart, progress in the treatment of sepsis-induced myocardial depression has been hampered by a poor understanding of the molecular mechanisms involved in this condition.…”
mentioning
confidence: 82%